MAKNA FILOSOFI HARI RAYA GALUNGAN PADA ERA GLOBALISASI - I Nyoman Suka Ardiyasa (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2018)
Galungan celebrated by Hindus every 210 days. This celebration is in accordance withthe calculation wuku calendar system. Meaning of Galungan is the day that the victory of dharmaagainst adharma is commemorated with devotional prostration harness presented to Ida SangHyang Widi Wasa. But over time, especially in this globalization era many shifts of meaning ofthe celebration of Galungan. Trend-oriented globalization are just looking for satisfaction ofworldly (material and pleasure oriented) background by the philosophy of hedonism, a worldlyview of life-oriented and do not believe in natural law or hereafter karmaphala. In Hinduism, itis stated that if the orientation of the human and material just sheer pleasure, the men werefound only satisfactory kama (lust). One phenomenon that we can see in the celebration of theFeast Survey Online.com with the holding Bazzar trens globalization as a venue to celebrate thevictory of dharma against adhrama, but we know the Bazzar Galungan is synonymous withliquor such as beer, even complete with arena-like jojing discotheque. So it is not uncommon inthe circuit implementation of the bazaar Galungan always colored noise, both in small scaleand has been entered in criminal cases, of course this is not in accordance with the sprit of theday Galungan. Besides, at the time of celebration penjor survey in the several places is a veryimportant part in carrying out the celebration of Galungan. Penjor is the meaning of the expressionof gratitude presented to Ida Sang Hyang Widi Wasa grown to deliver to the earth to him, butlater can be found in several places penjor positioned as a showcase to seemed to show thattheir owners are coming from the class and respected, as well as additions of ornament whichdoes not correspond with the philosophies inherent in the meaning penjor.